Karakteristik Tomat Ceri Selama Penyimpanan Pada Perlakuan Rasio Komposit Edible Coating Pati Singkong-Kitosan - Risty, Kadek Septia Andia; Hartiati, Amna; Yoga, I Wayan Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Cherry tomatoes have a short shelf life due to their climacteric nature, making them highly susceptible to postharvest damage. One effort to extend shelf life and maintain quality is the application of an edible coating. This study aimed to determine the effect of cassava starch-chitosan-based composite edible coating ratios on the characteristics of cherry tomatoes during storage and to identify the optimal ratio that best preserves tomato quality. The research design used complete randomized design (RAL) with treatments consisting of composite ratios of cassava starch-chitosan edible coating, namely 10:90 (PK1), 30:70 (PK2), 50:50 (PK3), 70:30 (PK4), and 90:10 (PK5), with three replications, resulting in 15 experimental units. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). Coated cherry tomatoes were observed until spoilage occurred. The variables measured included weight loss, fruit firmness, total soluble solids, and vitamin C content. The results showed that the composite ratio of cassava starch–chitosan edible coating had a significant effect on weight loss and vitamin C content on day 4 to 8 of storage, as well as firmness and total soluble solids on day 5 to 8. The best treatment was the 50:50 ratio, which weight loss of 17.73%, fruit firmness of 12.89 N, total soluble solids of 6.7°Brix, and vitamin C of 12.71 mg/g on the 9th day of storage.